Consequences for Counterfeiting and Distributing of Counterfeit Vaccines under Jināyah and Criminal Law: A Comparative Study - Syatar, Abdul; Abubakar, Achmad; Fauzan, Ahmad; Kurniati; Hukpar, Darhan Sutradi (Al-Manahij: Jurnal Kajian Hukum Islam, 2023)
The proliferation of counterfeit vaccinations was producing significant public health problems and was related with legal issues. This article compared the sanctions imposed by Islamic criminal law and national legislation on counterfeiters and distributors of fake vaccines. Several rules and regulations control the use and distribution of vaccinations in Indonesia. In accordance with Articles 196 and 197 of Law Number 36 of 2009 on Health, the criminal act of distributing counterfeit vaccines is punishable by a maximum prison sentence of ten years and a maximum fine of one billion in IDR. As opposed to Article 197, which stipulates a maximum punishment of 15 years in prison and a maximum fine of Rp. 1,500,000,000,000. counterfeiting and distributing counterfeit vaccines are considered serious crimes in both Islamic criminal law and Jināyah. The punishment for these crimes varies depending on the severity of the offense and the harm caused to society. In both systems of law, the punishment can range from fines and imprisonment to the death penalty. It is important to note that these punishments are intended to deter individuals from engaging in these crimes and protect public health and safety. It was believed that the government would increase legislation addressing the punishment of counterfeiters and drug dealers, who can harm the Indonesian national character.